Heparin Resistance (Case Report) - Ilksen Toprak, Huseyin; Kadir But, A.; Borazan, Hale; Ozcan Ersoy, M. (Annals of Medical Research, 2021)
None
Keywords: Anticoagulant, Heparin, Antitrombin III, Surgery, Cardiac.